Relativistic calculations of screening parameters and atomic radii of neutral atoms - Guerra, M. (2019)
Calculations of the effective nuclear charge for elements with 1≤Z≤118 have been performed in a Dirac–Fock approach including all relativistic effects as well as contributions from quantum electrodynamics. Maximum charge density for every subshell of every element in the periodic table was also computed in the same framework as well as atomic radii based on the total charge density. Results were compared with the extensively cited works of Clementi et al., obtained in the 1960s with Roothan's self-consistent-field method.